Increasing presence of Bigg’s killer whales and changing seasonality of Southern Resident killer whales in Washington waters - Zoe R. Rand; Laura E. Koehn; Alexis Morrigan; M. Bradley Hanson (PLoS ONE, 2026)
Two ecotypes of killer whales ( Orcinus orca) occur in the Washington waters of the Salish Sea: endangered, fish-eating Southern Resident killer whales (SRKW), made up of three family groups J-, K-, and L-pods, and marine-mammal-eating Bigg’s killer whales. Although these ecotypes overlap in space, they respond to different ecological processes, face different threats, and have different management priorities. Understanding how their habitat use has changed over time can give us insight into changes in the ecosystem that may be affecting these populations and enable spatially explicit management strategies. Using killer whale detections in Washington waters from 1978–2022, we fit species distribution models to SRKW and Bigg’s killer whales, to understand spatiotemporal trends in killer whale presence. We found that SRKW presence was quite variable, but they were most likely to be present in 2001 (70% average probability of presence) and least likely to be present in 2019 (23% average probability of presence). Bigg’s presence increased over time, from 4% average probability of presence in 1978 to 66% probability of presence in 2022. The decrease in SRKW probability of presence in recent years was most likely driven by K- and L-pods which showed a decline in average annual probability of presence since 2017, while the average annual probability of presence remained high for J-pod. On a seasonal level, SRKW presence has decreased in summer months (June-August) since 2016, while Bigg’s presence has continued to increase in all months. As Bigg’s presence has increased in Washington waters, SRKW and Bigg’s habitat use has increasingly overlapped, especially in the Puget Sound. Since 2011, the probability of Bigg’s presence has increased in the Whidbey Basin while SRKW presence has decreased. Additionally, in October – January, SRKW and Bigg’s have an equal probability of being present throughout the Central Basin. These models can be used to determine optimal times and areas for management actions to limit exposure of anthropogenic disturbances to SRKW and Bigg’s killer whales.